2016
DOI: 10.18001/trs.2.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SPECTRUM Variable Nicotine Research Cigarettes

Abstract: Objective To provide researchers an extensive characterization of the SPECTRUM variable nicotine research cigarettes. Methods Data on cigarette physical properties, nicotine content, harmful and potentially harmful constituents in the tobacco filler was compiled. Results Data on physical properties, concentrations of menthol, nicotine and minor alkaloids, tobacco-specific nitrosamines, polycyclic aromatic hydrocarbons, ammonia, and toxic metals in the filler tobacco for all available varieties of Spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 21 publications
1
55
1
Order By: Relevance
“…SPECTRUM Tobacco Product Master File Codes used for UNC group (non-menthol/menthol) are NRC600/NRC601 or NRC602 a These are averages of menthol/non-menthol cigarettes at each level based on estimated 0.7 g tobacco content per cigarette and nicotine concentrations based on Richter et al (2016) [54] b Approximate mean nicotine content and concentration of commercially available cigarettes based on Connolly et al (2007) [62]…”
Section: Methodsmentioning
confidence: 99%
“…SPECTRUM Tobacco Product Master File Codes used for UNC group (non-menthol/menthol) are NRC600/NRC601 or NRC602 a These are averages of menthol/non-menthol cigarettes at each level based on estimated 0.7 g tobacco content per cigarette and nicotine concentrations based on Richter et al (2016) [54] b Approximate mean nicotine content and concentration of commercially available cigarettes based on Connolly et al (2007) [62]…”
Section: Methodsmentioning
confidence: 99%
“…Although some toxicants may change as a result of nicotine reduction (eg, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone), most harmful and potentially harmful constituents are similar to commercial or reference cigarettes,14 15 resulting in largely unchanged urinary biomarkers of toxicant exposure following short-term use (ie, when cigarettes per day remain relatively stable) 15–18. Longer studies that have resulted in fewer cigarettes per day have observed parallel decreases in urinary biomarkers of toxicant exposure,9 highlighting how reduction in harm is secondary to changes in behaviour 19…”
Section: Evidence-based Potential Benefits Of Reducing Nicotine In CImentioning
confidence: 99%
“…LNCs with a range of reduced nicotine levels have been marketed in the U.S. (e.g., Quest cigarettes (Strasser et al, 2007)), and often have been used in studies of smoking behavior and nicotine addiction (e.g., Spectrum cigarettes (Richter et al, 2016)). Smoking LNCs in the same manner and frequency as typical cigarettes results in the same exposure to harmful chemicals other than nicotine, and could lead to increased exposure to harmful chemicals if smokers modify smoking behavior to compensate for lower nicotine levels (Hatsukami et al, 2010; Strasser et al, 2007; O'Connor et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%